E-recruitment in Sarawak state civil services: a study of perceptions government employees / Noradila Mohd Nasir and Siti Khatizah Safiyuddin - Mohd Nasir, Noradila; Safiyuddin, Siti Khatizah (2007)
With the proliferation and continuous advancement and growth in Internet technology, e-recruitment as business activity is growing globally. The low cost e-recruitment has also attracted many corporate companies to capitalize this technology for recruitment. Millions of jobseekers are posting their resumes to the popular third party e-recruitment job sites. E- recruitment has the potential to change some of the ‘traditional’ recruitment sources. With this continuous growth of jobseekers population using this technology for job search, this research aims to analyses and predict the civil service’s perceptions of e-recruitment accessibility, selecting or recruiting a suitable candidates and analyzing whether e- recruitment faces the difficulties in reconciling online and offline processes. A random sample of 150 civil services at MASJA and Bangunan Sultan Iskandar were given the questionnaires. From the research we found that the accessibility of our respondents is in moderate level. Then, we also found that e-recruitment has average risks to select or recruit suitable or qualified candidates. And, last but least, it shows that most of the respondents’ opinion said that using online process is give more advantages compared than offline process.